Structural and morphological evolution of metal oxide nanoparticles synthesised via sol-gel auto-combustion - Zaid, H.M. (Inderscience Enterprises Ltd., 2017)
Metal oxide nanopowder synthesis for pure ZnO and α-Al2O3 was carried out by a simple and fast sol-gel auto-combustion method. Thermogravimetric analysis (TGA) was performed to confirm the phase purity of nanopowder. The transformation of crystalline phases of as-synthesised nanopowders was then investigated through X-ray diffraction (XRD) in terms of their crystallinity and crystallite size. Subsequently, a detailed transmission electron microscopy (TEM) investigation and surface area study revealed the crystallographic alterations and morphological information even at lattice scale. From selected area electron diffraction (SAED) pattern has specified the d-spacing and corresponding planes which co-include with the XRD d-spacing and planes. The existence of distinctive bonds was studied by applying Fourier-transform infra-red (FTIR) spectroscopy. The transformation of fascinating microstructure and phase formations has been presented to explicate the evolution of an amorphous state into different crystalline phases with increased calcining temperature. Copyright © 2017 Inderscience Enterprises Ltd.